Digital Transformation and Corporate Social Responsibility for Impact Measurement: A Literature Review - Edralene M. Toñacao; Anik Yuesti; Joel Arante Alve (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Digital transformation is reshaping how firms define, capture, verify, and communicate the social and environmental consequences of corporate activity. This integrative literature review examines how digital technologies influence corporate social responsibility impact measurement and distinguishes such measurement from sustainability disclosure and ESG ratings. The synthesis identifies five interdependent dimensions: strategic intent and materiality, digital data infrastructure, analytics and traceability, measurement and reporting design, and governance with stakeholder feedback. Artificial intelligence, big data analytics, Internet of Things sensors, blockchain, cloud platforms, and machine-readable taxonomies can improve timeliness, granularity, traceability, and comparability. However, digitalization alone cannot establish causal impact, ensure data quality, prevent greenwashing, or eliminate ESG rating divergence. Effective measurement requires theories of change, outcome-oriented indicators, interoperability, assurance, privacy protection, responsible artificial intelligence, and stakeholder participation. The review proposes an integrative framework and five-level maturity model, with particular relevance to emerging economies, the Philippines, and other digitally developing contexts worldwide.